Evidence-based practices in developing and maintaining clinical nurse preceptors: An integrative review. (October 2022) - Smith, Lisa C.; Watson, Heather; Fair, Linda; Carter, Grace; Mackay, Periwinkle; Lykens, Kelly; Bradstock, Jackie; Arnold, Kristen; Whalen, Madeleine
Abstract: Objectives: This integrative review of literature explores the best practice for establishing and maintaining a hospital-based nurse preceptor program. The intent is to provide nurse leadership and educators with guidance for optimizing preceptor programs in order to improve patient, staff, and organizational outcomes. Design: The project team conducted an integrative review of literature to inform best practice using the Johns Hopkins Evidence-Based Practice Model and Guidelines. Data sources: Data sources included the PubMed, CINAHL, and Cochrane databases. Review methods: Each applicable article underwent a rigorous review and appraisal by the project team. The team used the Johns Hopkins Evidence-Based Practice Model to guide the appraisal process and to synthesize results to generate a comprehensive list of recommendations. Results: The search yielded 115 unique articles that answered the evidence-based practice question. What are best practices for establishing and maintaining a hospital-based nursing preceptor program? Due to the abundance of data, the practice question was divided into three separate sub questions that explored preceptor development, continuous preceptor support, and essential competencies of preceptors. Relevant evidence included one level I article, seven level II articles, and one level IV article. Most of the evidence was found in articles ranking as level III (n = 54) and level V (n = 52). Conclusions: Many preceptorship themes and recommendations resonate throughout multiple levels of evidence. Recommendations include implementing an evidence-based, standardized curriculum that features diverse teaching modalities, critical thinking, and clinical reasoning. Common themes in the literature echo that preceptors need ongoing education, training, and support to improve nursing satisfaction, retention, and the quality of nursing care.